2004
DOI: 10.1111/j.1365-2575.2004.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Systems development approach: transcending methodology

Abstract: This paper presents the findings of an empirical study investigating the nature of the process of information systems development. These findings are used to identify systems development approach, which extends understanding of the information systems development process beyond the levels of methodology and technical expertise. The term approach expresses the rich, varied, and complex ways in which professionals deal with development situations. The term transcends methodological components -which can be combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Other examples where one may speculate about the use of the paradigm include Goulielmos (2004) as well as Baskerville and Pries-Heje (2004).…”
Section: Articlementioning
confidence: 98%
See 1 more Smart Citation
“…Other examples where one may speculate about the use of the paradigm include Goulielmos (2004) as well as Baskerville and Pries-Heje (2004).…”
Section: Articlementioning
confidence: 98%
“…References on axial coding Quote(s) Goulielmos (2004) Strauss and Corbin (1990) 'Axial coding helped to develop links among categories. With the identification of core categories, analysis shifted from a process of initial exploration to a process of elaborating key concepts and their properties' (p. 366) Kirsch (2004) Strauss and 'Open coding was followed by axial coding , which is a process of linking similar concepts into categories' (p. 381) Lindgren et al Strauss and Corbin (1990) 'The transcribed material was analyzed by using the open and axial coding techniques )' (p. 445) Lim et al (2005) Orlikowski (1993) 'Through the procedure of open and axial coding, we identified common patterns of interest across subjects from the unprocessed raw data.…”
Section: Articlementioning
confidence: 99%
“…Historically, it is often the case that even if the methodology is executed correctly, the resultant information system can fail because of a misapplied method . After all, there are a number of activities as a part of the ISD process that emerge outside of the scope of methodology and have significant impact (Goulielmos, 2004). To overcome this limitation, it is important that the developers remain engaged in the true, messy process of ISD and not let them invest too heavily in the tools or method itself.…”
Section: Limitations Of Sommentioning
confidence: 99%
“…No SDM can meet the contingencies of every project (Avison & Fitzgerald, 2003). Such contingencies can be stakeholders' contextual preferences and skills on method use, previous skills and IS development (ISD) approach held by the professional developers, industry standards on particular domains, and historical reasons in the organization where the system is being developed (Fitzgerald, 1997;Fitzgerald et al, 2003;Goulielmos, 2004). Proponents of situation-specific method engineering (Kumar & Welke, 1992;Brinkkemper et al, 1996;Tolvanen, 1998) recognize this pragmatism and propose systematic ways of utilizing and improving SDMs in context with method engineering tools.…”
Section: Introductionmentioning
confidence: 99%